Enhanced biosynthesis of physiologically active vitamin D3 by constructing recombinant Escherichia coli BL21 with a multienzyme system. (February 2023) - Fu, Bing; Yang, Liuzhen; Chen, Qingwei; Zhang, Qili; Zhang, Lei; Yu, Ping
Abstract: In this study, a recombinant E. coli strain with the multienzyme system of the vitamin D3 hydroxylase CYP105A1, the electron transport respiratory chain Fdx-FdR and the key enzymes (Glk-Zwf) in the cyclic regeneration of the coenzyme NADPH was constructed for the efficient hydroxylation of VD3 to prepare physiologically active 25(OH)VD3 and 1α, 25(OH)2 VD3 . The constructed recombinant E. coli strain with a multienzyme system was demonstrated to possess hydroxylation capability for VD3 . The hydroxylation reaction of VD3 was carried out under optimal conditions. The highest concentration of the intermediate product 25(OH)VD3 was 58.92 mg/L with a yield of 11.31 %. The highest concentration of the final product 1α, 25(OH)2 VD3 was 90.23 mg/L with a yield of 16.7 %. Ultimately, 395.92 mg/L 25(OH)VD3 and 272.21 mg/L 1α, 25(OH)2 VD3 were produced by further substrate fed-batch experiments. This study contributes to the preparation of physiologically active 25(OH)VD3 and 1α, 25(OH)2 VD3 by whole-cell biocatalysis of VD3 via the constructed recombinant strain. Graphical Abstract: ga1 Highlights: The coenzyme NADPH regeneration system in E. coli was established. The recombinant E. coli with a multienzyme system was constructed. The constructed E. coli could catalyze vitamin D3 to its active forms. Fermentation conditions of the recombinant E. coli were explored. This study contributes to the preparation of physiologically active vitamin D3 .